Computer architecture from the stone age to the quantum age - Fox, Charles (No Starch Press, 2024)
"Covers the inner workings of the computer, from the transistor level up to complete CPUs, memory, and beyond, as well as more recent developments, like parallel and quantum architectures. Each chapter includes hands-on exercises and additional resources for exploring topics further"--